Application of Augmented Reality Technology in the SDN 1 Sanur Building Recognition Application - Vyasa, I Made Satya; Wibawa, I Gede Arta (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
This study aims to build an application to introduce the Sumerta 1 public elementary school building. This research uses AR (Augmented Reality) technology, which with this technology makes it possible to display an object in virtual form in a real world view. The method used in this application is marker-based which identifies the pattern of a marker, in the application development itself the model used is the waterfall model. In the process of building this application, using the Vuforia software development kit (SDK) and Unity as the engine.